Sex differences in nicotine intake and relapse behavior in nicotine-dependent adult wistar rats - Chellian, Ranjithkumar; Behnood-Rod, Azin; Bruijnzeel, Adriaan W. (Frontiers in Pharmacology, 2024)
Introduction Tobacco use is highly addictive and the leading cause of premature mortality in the world. Long-access nicotine self-administration procedures in rats closely model human smoking behavior. However, significant gaps remain in our understanding of sex differences in the development of dependence and relapse in adult rats. Methods In the present study, we investigated operant responding for both nicotine and saline and the development of dependence in adult rats of both sexes. The rats had daily access to nicotine or saline for 6 h per day, 7 days per week. Dependence was assessed by evaluating precipitated and spontaneous somatic withdrawal signs, measuring locomotor activity in the small open field test, and assessing anxiety-like behavior in the large open field and elevated plus maze test. The sucrose preference test was used to determine if cessation of nicotine intake leads to anhedonia. It was also investigated if a period of forced abstinence affects nicotine-seeking behavior. Results This study showed that nicotine intake is higher in females than in males when given daily long access to nicotine. Daily nicotine self-administration led to more precipitated and spontaneous somatic withdrawal signs compared to saline self-administration, with no sex differences observed. In addition, cessation of nicotine intake led to a similar increase in activity in both males and females in the small open field test. However, cessation of nicotine intake did not increase anxiety-like behavior or cause anhedonia in either males or females. A time course analysis revealed that the nicotinic acetylcholine receptor antagonist mecamylamine affected nicotine intake differently in males and females, increasing intake in males and decreasing intake in females. Three weeks of forced abstinence led to an increase in nicotine and saline-seeking behavior. The rats exhibited more nicotine than saline seeking, and the females displayed more nicotine seeking than the males. Discussion The present findings demonstrate that females self-administer more nicotine and display more nicotine-seeking behavior than males. Furthermore, there were no sex differences in somatic withdrawal signs or activity during abstinence from nicotine. This work underscores the importance of considering sex differences across various aspects of addiction, including intake and relapse, when developing novel treatments for tobacco use disorder.